Recent Progress in Surface-Enhanced Raman Scattering for the Detection of Chemical Contaminants in Water - Bodelón, Gustavo; Pastoriza-Santos, Isabel (Frontiers in Chemistry, 2020)
Water is a matter of vital importance for all developed countries due to the strong impact on human health and aquatic, wetlands and terrestrial environments. Therefore, the monitoring of water quality is of tremendous importance. The enormous advantages that Surface-enhanced Raman scattering (SERS) spectroscopy offers, such as fingerprint recognition, multiplex capabilities, high sensitivity, and selectivity or non-destructive testing, make this analytical tool very attractive for this purpose. This minireview aims to provide a summary of current approaches for the implementation of SERS sensors in monitoring organic and inorganic pollutants in water. In addition, we briefly highlight current challenges and provide an outlook for the application of SERS in environmental monitoring.